Institutional Development Roadmap Handbook : Effective Design, Implementation and Evaluation of Project-led Institutional Development in the Transport Sector - Benamghar, Radia (World Bank, Washington, DC, 2019)
The World Bank (WB) is a vital source of financial and technical assistance across the transport sector in India. While financial resources and technical expertise are vital, they are not sufficient to promote sustainable development. This requires strong and durable institutions in client countries. In India’s transport sector, the extent to which sustained Institutional Development has been achieved varies significantly between projects. An understanding of the factors that led to successful outcomes and sustained institutional development is key to ensuring long-term added value of WB and client country investments. The Institutional Development Roadmap (IDR) presents a set of four interrelated tools that can help TTLs and IAs develop projects that coherently integrate infrastructure and ID, specifically focusing on building sustainable capacity to achieve both. The IDR contributes toward ensuring high impact, sustainable development by providing a systematic way to assess the environment for change and the capacity of IAs to achieve clear and measurable development outcomes. The IDRT is informed by the building blocks of political economy analysis, focusing on how power and resources are distributed and contested in specific areas of possible project support. It was designed to identify opportunities and challenges in these areas by addressing how formal and informal interests, incentives, and institutions support or prevent the reforms required for sustainable ID. The tools also recognize the importance of engaging key stakeholders (including citizens impacted by potential WB projects) in designing and implementing sustainable interventions that are achievable within the project life cycle and sustainable after the project closes.